Daring adventures in paint : find your flow, trust your path, and discover your authentic voice : techniques for painting, sketching, and mixed media /: find your flow, trust your path, and discover your authentic voice : techniques for painting, sketching, and mixed media. (2012) - Unknown
No abstract available